The Impact Of Perceived Feasibility And Perceived Desirability On Entrepreneurial Intention Among Undergraduate Students In Universitas Muhammadiyah Surakarta - Jauhar Masrury, Mukhamad; , Dr. Soepatini, SE., M.Si (2016)
This study adopted Entrepreneurial Intention Model from Linan and Rodriguez as a theoretical framework with the aim to determine the influence of perceived desirability and perceived feasibility on entrepreneurial intention among undergraduate students in UniversitasMuhammadiyah Surakarta. This research is quantitative research and used purposive sampling in taking sample. The sample size of this research is 83 respondents taken from final international students of UniversitasMuhammadiyah Surakarta. Confirmatory factor analysis and cronbach'salpha were used for validity and reliability respectively. Multiple regression analysiswas used to analyze the data in this research. The result of the research shows all variables have positive and significant value on entrepreneurial intention. This study also proposes suggestions for university students, the UniversitasMuhammadiyah Surakarta, and the government